MRI-guided ultrafocal HDR-brachytherapy for localised prostate cancer: median 4 year results of a feasibility study - Peters,M; van,Son MJ; Moerland,MA; Kerkmeijer,LGW; Eppinga,WSC; Meijer,RP; Lagendijk,Ir JJW; Shah,TT; Ahmed,HU; van,der Voort van Zijp JRN (International Journal of Radiation Oncology - Biology - Physics, 2019)
PurposeFor the treatment of localized prostate cancer, focal therapy has the potential to cure with fewer side effects than traditional whole-gland treatments. We report an update on toxicity, quality of life (QoL), and tumor control in our magnetic resonance imaging (MRI)-guided ultrafocal high-dose-rate brachytherapy cohort.Methods and MaterialsDisease status was evaluated by systematic biopsies and 3T multiparametric MRI. The brachytherapy implant procedure under fused transrectal ultrasound/MRI guidance was followed by a 1.5 T MRI for contour adjustments and catheter position verification. A single dose of 19 Gy was delivered to the tumor with a margin of 5 mm. Genitourinary (GU) toxicity, gastrointestinal (GI) toxicity, and erectile dysfunction (ED) were graded with the Common Terminology Criteria for Adverse Events version 4.0. QoL was measured with RAND-36, European Organisation for Research and Treatment of Cancer QLQ-C30 and PR25. International Prostate Symptom Scores and International Index of Erectile Function scores were obtained. Prostate-specific antigen level was monitored, with biochemical recurrence defined as nadir + 2 ng/mL (Phoenix).ResultsThirty patients with National Comprehensive Cancer Network low- (13%) to intermediate-risk (87%) prostate cancer were treated between May 2013 and April 2016. Median follow-up was 4 years. Median age was 71 years (interquartile range, 68-73) and median initial prostate-specific antigen level was 7.3 ng/mL (5.2-8.1). Maximum Gleason score was 4 + 3 = 7 (in 2 patients). All tumors were radiologic (MRI) stage T2. No grade >2 GU or >1 GI toxicity occurred. International Prostate Symptom Scores only deteriorated temporarily. Mild pretreatment ED deteriorated to moderate/severe ED in 50% of patients. Long-term clinically relevant QoL deterioration was seen in sexual activity and tiredness, whereas emotional and cognitive functioning improved. At 4 years, biochemical disease–free survival was 70% (95% conf